1997
DOI: 10.1002/hep.510260621
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to tumor necrosis factor alfa attenuate hepatic necrosis and inflammation caused by chronic exposure to ethanol in the rat

Abstract: Tumor necrosis factor (TNF)alpha, a pivotal cytokine involved in inflammation, is produced primarily by Kupffer cells in the liver. It has been shown that inactivation of Kupffer cells prevents alcohol-induced liver injury; therefore, the purpose of this study was to determine if neutralizing anti-TNF-alpha antibody is also effective. Male Wistar rats were exposed to ethanol (11 to 12 g x kg(-1) x d[-1]) continuously for up to 4 weeks via intragastric feeding using an enteral feeding model. Before ethanol expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
174
2
4

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(186 citation statements)
references
References 43 publications
6
174
2
4
Order By: Relevance
“…The results of this study could be relevant, since it could provide useful human data to research groups devoted to the study of ALD. Importantly, some of the results obtained in our study differ from those obtained in rodents exposed to alcohol (ie, the lack of hepatic upregulation of TNFα and its specific receptors) 4 5. These discrepancies between human and experimental data reinforce the need to develop an experimental model that reproduces all the features of AH.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The results of this study could be relevant, since it could provide useful human data to research groups devoted to the study of ALD. Importantly, some of the results obtained in our study differ from those obtained in rodents exposed to alcohol (ie, the lack of hepatic upregulation of TNFα and its specific receptors) 4 5. These discrepancies between human and experimental data reinforce the need to develop an experimental model that reproduces all the features of AH.…”
Section: Discussioncontrasting
confidence: 75%
“…The most relevant agonists include TNFα, TNF-like weak inducer of apoptosis (TWEAK) and Fas ligand. Studies from experimental models of alcoholic liver injury have implicated TNFα, Fas ligand and their receptors in liver damage and remodelling 4 5 19 20. Little is known on the role of TWEAK and its specific receptor Fn14.…”
Section: Introductionmentioning
confidence: 99%
“…We found that patients with both MetS and NAFLD showed a significant increase in serum level of both TNF-α and IL-6. TNF-α level correlates well with liver disease severity, as demonstrated by reported studies (Iimuro et al, 1997). Much evidence supports the pathophysiological role of TNF-α in NAFLD, such as higher TNF-α mRNA expression in nonalcoholic steatohepatitis (NASH) patients with hepatic fibrosis, and increased prevalence of TNF-α polymorphisms in NAFLD patients (Copaci et al, 2006).…”
Section: Discussionmentioning
confidence: 73%
“…Although this cytokine exerts pleiotropic effects in the context of the liver, its major effects are associated with the regulation of hepatocyte proliferation and apoptosis and the induction of inflammatory response [82,83]. The biological effects of TNF-are mediated by its interaction with two plasma membrane receptors: TNF-R1 and TNF-R2.…”
Section: Tnf-mentioning
confidence: 99%